Longitudinal alignment effect of graphene oxide nanoribbon on properties of polyimide-based carbon fibers. (15th October 2022) - Kim, Junghwan; Kim, Sungyong; Heo, So Jeong; Kim, Seo Gyun; You, Nam-Ho; Chae, Han Gi; Kim, Hwan Chul; Ku, Bon-Cheol
Abstract: Polyimide/graphene oxide nanoribbon (PI/GONR) composite fibers were prepared by wet spinning. The unfolded GONRs by the intense drawing of fibers maximized their contribution to enhance mechanical and conductivity properties. The composite fibers were spun with an optimal drawing ratio of 18, followed by carbonization at 1200 and 1400 °C, respectively. The PI/GONR (0.1 wt%) composite fibers carbonized at 1400 °C have the highest tensile strength (2.12 ± 0.45 GPa), which was 35% increase compared to PI-based carbon fibers that are carbonized at 1400 °C. In addition, electrical (604 ± 33 S/cm) and thermal conductivity (12 ± 0.56 W/m·K) improved by 58% and 32%, compared to PI-based carbon fibers carbonized at 1400 °C. These values are comparable with 625 S/cm of electrical conductivity and 9.4 W/m·K of thermal conductivities of Toray carbon fiber (T700). Optimal drawing conditions can maximize orientation and packing density, resulting in maximum performance with a small amount of GONR (0.1 wt%). This significant improvement in macroscopic properties confirms wide possibilities for the manufacture of GONR composite fibers to acquire carbon fibers with excellent physical properties produced through the addition of GONR. Graphical abstract: Image 1